Incomplete or failed thrombectomy in acute stroke patients with Alberta Stroke Program Early Computed Tomography Score 0–5 – how harmful is trying?. (26th June 2020) - Broocks, G.; Flottmann, F.; Schönfeld, M.; Bechstein, M.; Aye, P.; Kniep, H.; Faizy, T. D.; McDonough, R.; Schön, G.; Deb‐Chatterji, M.; Thomalla, G.; Sporns, P.; et al.
Abstract : Background and purpose: It is currently unknown whether mechanical thrombectomy (MT) for ischaemic stroke patients with low initial Alberta Stroke Program Early Computed Tomography Score (ASPECTS) is clinically beneficial or even harmful. The purpose of this study was to investigate whether failed or incomplete MT in acute large vessel occlusion stroke with an initial ASPECTS ≤ 5 is associated with worse clinical outcome compared to patients not undergoing MT. Methods: This observational cohort study included a consecutive sample of patients with anterior circulation stroke and initial ASPECTS ≤ 5 admitted between March 2015 and August 2019. Failed recanalization was defined as Thrombolysis in Cerebral Infarction (TICI) score 0–2a, and incomplete recanalization as TICI 2b. Clinical outcome was assessed using the modified Rankin Scale (mRS) at 90 days defining very poor clinical outcome as mRS > 4. Results: One hundred and seventy patients were included. Ninety‐nine patients underwent MT and 71 patients received best medical treatment only. Clinical outcome after failed or incomplete MT (TICI 0–2b) was significantly better compared to patients with medical treatment only (median mRS 5, interquartile range 4–6 vs 5–6, P = 0.03). In multivariable logistic regression analysis, failed or incomplete MT (TICI 0–2b) showed a significantly reduced likelihood for very poor outcome (odds ratio 0.39, 95% confidence interval 0.19–0.83, P = 0.01). Failed MT (TICI 0–2a) was not associated with a worse outcome compared to best medical treatment. Conclusions: Patients with failed or incomplete recanalization results (TICI 0–2b) showed a reduced likelihood for very poor outcome compared with those who did not receive MT. Evidence from randomized trials is needed to confirm that even failed or incomplete MT is not harmful in these patients.